Hepatocellular Carcinoma versus Other Hepatic Malignancy in Cirrhosis: Performance of LI-RADS Version 2018 - Kim, Yeun-Yoon; Kim, Myeong-Jin; Kim, Eun Hwa; Roh, Yun Ho; An, Chansik (Radiology, 2019)
Purpose To evaluate the diagnostic accuracy of the Liver Imaging Reporting and Data System (LI-RADS) version 2018 for differentiating between hepatocellular carcinoma (HCC) and other (hepatic) malignancy (OM) in patients with liver cirrhosis. Materials and Methods From 2008 to 2017, 55 patients with untreated OM and liver cirrhosis were eligible for this retrospective case-control study (mean age, 58 years ± 10 [standard deviation] [range, 32-79 years], with 45 men [mean age, 58 years ± 11] and 10 women [mean age, 62 years ± 7]). Control subjects consisted of 165 treatment-naive patients with HCC and liver cirrhosis (mean age, 58 years ± 10 [range, 29-80 years], with 134 men [mean age, 58 years ± 9] and 31 women [mean age, 59 years ± 11]). Two radiologists blinded to the final diagnosis independently determined the presence of LR-M features and major HCC features (non-rim arterial phase hyperenhancement, non-peripheral washout, and enhancing capsule). The diagnostic performances of each feature, the LR-M criteria (probably or definitely malignant, but not specific for HCC), and the LR-5 criteria (definitely HCC) were calculated and compared by using the generalized estimating equation method. Results Individual LR-M features had a sensitivity of 9%-71% and a specificity of 83%-97% for the diagnosis of OM. Major features of HCC had a sensitivity of 62%-83% and a specificity of 69%-89% for the diagnosis of HCC. The LR-M criteria had a sensitivity of 89% (95% confidence interval [CI]: 81%, 97%) for diagnosing OM, with a specificity of 48% (95% CI: 40%, 56%). The LR-5 criteria had a sensitivity of 74% (95% CI: 67%, 81%) for diagnosing HCC, with a specificity of 89% (95% CI: 81%, 97%). The accuracy of the LR-5 criteria was higher than that of the LR-M criteria (78% [95% CI: 72%, 83%] vs 58% [95% CI: 52%, 65%], P <. 001). Conclusion The LR-5 criteria as well as the LR-M criteria can effectively distinguish hepatocellular carcinoma from other hepatic malignancy in patients with liver cirrhosis. © RSNA, 2019 Online supplemental material is available for this article. See also the editorial by Furlan in this issue.